Academic Resilience in the Face of Internet Challenges: A Narrative Analysis of Tertiary Students’ Experiences - Akmad, Abusailan (Journal of Interdisciplinary Perspectives, 2024)
This qualitative research explored internet connectivity's influence on tertiary students' academic lives in Palimbang, Sultan Kudarat. It highlighted the challenges posed by unstable internet connections, students' resilience in adapting to them, the coping mechanisms employed by the students in accessing unstable internet connections, and the emotional toll it took on them. This paper used narrative analysis to interpret the data set from the participants. Through in-depth interviews, ten (10) participants shared their experiences of grappling with sluggish and unstable internet connections, hindering access to educational resources, and disrupting collaborative learning endeavours. Despite these challenges, students demonstrated resilience, employing strategies like accessing the Internet during off-peak hours and utilizing offline resources. However, these adaptations came with their own set of drawbacks, including sleep deprivation and financial strain. Emotionally, frustration with unreliable internet connectivity was palpable, yet students recognized the Internet's transformative role in their learning journey. The paper underscored the vital importance of reliable Internet infrastructure in rural education, advocating for concerted efforts to bridge the digital divide and ensure equitable access to quality Internet services. Ultimately, it highlighted the resilience of rural students while emphasizing the urgent need to improve the digital infrastructure to support their academic endeavors in the digital age.